Re: Providing material samples for the structure construction, pre-opening and pre-embedding work - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the reply on providing material samples for the structure construction, pre-opening and pre-embedding work for BRACU new campus project.